Filsafat Ekonomi Islam dalam Ruang Mikro (Kajian Mendalam atas Epistemologi, Ontologi, dan Aksiologi Koperasi Syariah Qurrata A’yun) - Witri, Witri; Lutfi, Ahmad; Iska, Syukri (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2026)
This study aims to analyze the application of Islamic economic philosophy covering the dimensions of epistemology, ontology, and axiology within Koperasi Syariah Qurrata A’yun. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, direct observations, and a review of the cooperative’s formal documents. The findings indicate that, in terms of epistemology, the cooperative refers to DSN-MUI fatwas and basic principles of Islamic jurisprudence; however, the transmission of Sharia knowledge remains unstructured, resulting in low member literacy and suboptimal Sharia oversight. From an ontological perspective, the cooperative conceptualizes wealth as a trust (amanah) and fosters strong familial relations, evident in its transparent margin-setting and humanistic approach to resolving financing problems. Nonetheless, financing practices are still influenced by urgent consumptive needs and limited administrative capacity. In the axiological dimension, values of justice, deliberation, public benefit (maslahah), and anti-exploitation are reflected through the Annual Member Meeting (RAT), fair pricing mechanisms, ethical service delivery, and social support programs, although challenges such as moral hazard and limited human resources persist. Overall, the cooperative embodies the core values of Islamic economics, yet requires strengthened literacy systems, Sharia-based standard operating procedures, and improved governance to ensure a more consistent, profound, and sustainable implementation of Islamic economic philosophy.